Irregular Periapical Radiopacity in Mandibular Premolars and Molars. (20th February 2014) - Warrier, S. Aravind; Vinayachandran, Divya
Abstract : Increased deposition of cementum is observed in a wide number of both benign and malignant conditions. Many cases are often diagnosed during routine examination as an incidental finding. Diagnosing correctly without confusing it with other similarly appearing lesions, thus avoiding subjecting the patient to unnecessary investigations and stress, is of prime importance. We report one such case, where the patient presented with the routine complaint of a painful tooth, during the investigation of which he was also diagnosed with hypercementosis affecting the mandibular second premolars and molars bilaterally. The literature review reveals that not many cases of hypercementosis are frequently reported.